Eu e minha escola - Lourenço, Daniela Santana; Lourdes , Dayane Freitas de; Dan , Edircelia Matos; Cruz , Florisvaldo Gonçalves da; Silva , Maria Sinforosa Martin da; Dan , Marlene Amaral de Matos; Carraro, Márcia Regina Simpioni; Tinerel, Nandara Maciel Leite (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf